Who wants to be able to do references properly and be unemployed? STEM student writing and employer needs - Yvon Appleby (Association for Learning Development in Higher Education (ALDinHE), 2012)
The issue of graduate writing is one that has attracted much focus and debate in higher education, particularly around maintaining Ã¢â¬Ëacademic standardsÃ¢â¬â¢ at a time of expansion in this sector. The need to develop academic skills, including writing, for higher education study has increasingly been linked to the skills that graduates need to gain employment (Davies et al., 2006). This raises the question of whether the type and purpose of writing within university programmes is different to, and possibly in tension with, writing required for employment after university. This is a point raised by recent research (Day, 2011) which shows that students studying STEM (Science, Technology, Engineering, and Maths) subjects are more confident with oral rather than writing skills. The material discussed in this article is part of a two-year mixed method study looking at literacies, including writing, which undergraduate students develop at university, and the relationship of these literacies to employability. This article focuses on six first-year STEM students studying Forensic Science and Computing Science within the larger study. The qualitative data, gathered through repeat interviews, is discussed in relation to a small sample of employers and alumni working in science-based industries describing writing for transition into work and for on-going employment. The project therefore provides a useful student insight into writing, comparing this with employer expectations and the experience of alumni who have made the transition into work. What emerges from our study is the need to see writing at university as part of a wider communicative repertoire supported by a social and cultural approach to situated writing. This approach is more than simply skills based and is one that encourages and develops social as well as academic learning. We argue that such an approach, added to by technical skills support, enables greater engagement and success with learning in addition to enhancing employability.